Multilingual, bilingual, and monolingual Arabic teachers' development of learner self‐regulation and language awareness in the Emirates. (1st March 2021) - Tang, Fei; Calafato, Raees
Abstract: Multilingual learning and teaching have been receiving growing attention of late as many cities and states undergo significant demographic changes brought about by increasing levels of human migration. The onset of super‐diversity means that teachers often encounter students with very different language and cultural backgrounds in the classroom. This has created a new set of challenges and opportunities, especially concerning the teaching and learning of languages. As a result, research on language teaching and learning in super‐diverse contexts has acquired greater importance, yet the teaching of languages other than English (LOTE), specifically LOTE teacher beliefs and practices, has received comparatively little attention to date. To shed more light on teacher beliefs and practices as these concern the teaching of LOTEs to multilingual students, this study explored the extent to which 100 Arabic language teachers, working in UK‐curriculum secondary schools in the United Arab Emirates, used their students' multilingualism as a resource during lessons and developed their self‐regulation and language awareness through specific activities. The findings regarding the participants' efforts to develop their students' self‐regulation and language awareness revealed an unexpected, negative correlation between their degree of multilingualism and their reported practices. The Challenge: Foreign language teaching in super‐diverse contexts often consists of multilingual teachers and students from diverse backgrounds. How do teachers navigate and harness this super‐diverse multilingual environment when teaching languages other than English? This article explores Arabic teachers' use of multilingualism as a resource in schools in the United Arab Emirates.